59 Polychlorinated biphenyls and depression – first hints for a pathomechanism via the thyroid and dopamine system in humans. (24th April 2018) - Gaum, PM; Gube, M; Esser, A; Schettgen, T; Soares Quinete, N; Putschoegl, FM; Kraus, T; Lang, J
Abstract : Introduction: After PCB (polychlorinated biphenyls) exposure the development of depression has been described (Fitzgerald, et al. 2008). In general, depressive symptoms are associated with lower dopamine concentration and disturbed thyroid function. Thyroxin (T4) is necessary for dopamine synthesis in the brain (Hassan, et al. 2013). Bound to transthyretin (TTR); T4 is transported into the brain. Since PCB can displace T4 by binding to TTR itself (Hamers, et al. 2011); the concentration of free T4 (fT4) increases under PCB exposure. This study investigates the interaction of PCBs and fT4 related to the dopamine metabolite homovanillic acid (HVA) as well as to depression in humans. Methods: This study is part of the HELPcB (Health Effects in high Level exposure to PcB) surveillance program. Altogether, 109 occupationally exposed individuals [m=101 (92.7%); age: mean=44, SD=12.8] participated at three yearly assessments. Individuals with thyroid- or dopamine-relevant medication were excluded. PCBs were measured in plasma (µg/L), fT4 in serum, HVA in urine and depression was assessed with the PHQ-9 (Löwe, et al. 2002). PCB-congeners were summed up to LPCB (lower-chlorinated), HPCB (higher-chlorinated) and dlPCB (dioxin-like). A sum variable was generated for the PHQ-9. The interactions of PCBs and fT4 related to HVA and depression were tested with mixed models. Result: Significant interactions related to HVA were found for all PCB-subtypes (e.g. LPCB: B=−0.5, p<0.01). Under high PCB-exposure high fT4 levels are associated with a lower HVA concentration and vice versa. The interaction related to depression was only significant for LPCB (B=0.1, p<0.01). More depressive symptoms were found for high PCB-exposure with increasing fT4 level and vice versa. Discussion: The interactions related to HVA support the postulated pathomechanism via TTR. Individual and environmental factors may be a reason that the interactions for the behavioural outcome of depressive symptoms were only partially confirmed.